A Critical Study of the Halal Tourism Industry in Ora Beach, Central Maluku, and Its Impact on the Community's Economy - Marasabessy, Andi Ismail (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This research was conducted to identify the factors that drive individuals to visit Ora Beach. Additionally, the study aims to understand consumer perceptions after visiting Ora Beach and to assess the impact of Ora Beach on the local economy. The research used a mixed-methods approach. The results indicate that tourist facilities and halal attributes are the main factors influencing tourists to visit this destination. Tourists have a positive perception of Ora Beach and plan to revisit in the future. Furthermore, the presence of Ora Beach has created opportunities for the local community to improve their economy by engaging in the tourism sector at Ora Beach. The government, as the authority, needs to be directly involved and recognize the potential of the tourism opportunities, especially those offered by Ora Beach